Kompleksitas Kontrak Di Era Industri Sepak Bola Global (Perspektif Klub Sepak Bola Liga 1 Indonesia) - Mahendra Putra Kurnia; Emilda Kuspraningrum; Rika Erawaty; Grizelda Grizelda; Sofwan Rizko Ramadoni (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
Football has developed in such a way as to become an industry involving many actors and a huge economic turnover. Along with the development of the football industry, the legal relationship of the actors outlined in the contract is increasingly complex. The purpose of this paper is to describe the contractual complexities faced by professional football clubs in Indonesia. Using doctrinal research methods supported by a participatory approach, an understanding was obtained that each Liga 1 Indonesia football club at least interacts with 7 (seven) types of contracts where each contract has a different format, substance, and choice of law. Therefore, every professional football club in Indonesia is required to be able to adapt to the development of the global football industry, especially for legal consultants in each club must improve their knowledge and ability to draft contracts in order to protect the interests of the club. Keywords: Football industry; Contract; Football club, Choice of law Sepak bola telah berkembang sedemikian rupa menjadi sebuah industri dengan melibatkan banyak aktor dan perputaran ekonomi yang sangat besar. Seiring dengan perkembangan industri sepak bola, hubungan hukum para aktor yang dituangkan dalam kontrak semakin kompleks. Tujuan penulisan ini adalah untuk mendeskripsikan kompleksitas kontrak yang dihadapi klub sepak bola profesional di Indonesia. Menggunakan metode penelitian doktrinal ditunjang dengan pendekatan partisipatoris diperoleh pemahaman bahwa setiap klub sepak bola Liga 1 Indonesia setidaknya berinteraksi dengan 7 (tujuh) jenis kontrak dimana masing-masing kontrak memiliki format, substansi, dan pilihan hukum yang berbeda-beda. Oleh karena itu, bagi setiap klub sepak bola profesional di Indonesia dituntut untuk mampu beradaptasi dengan perkembangan industri sepak bola global, terutama bagi para konsultan hukum di setiap klub harus meningkatkan pengetahuan dan kemampuan dalam menyusun kontrak dalam rangka melindungi kepentingan klub.kata kunci: Industri sepak bola; Kontrak; Klub sepak bola, pilihan hukum